Preliminary Study of Surface Water Quality Based on DO and BOD Parameters in Pangandaran Reservoir - Lady Ayu Sri Wijayanti; Nurani Khoerunnisa; Helmalia Asri; Veronica Veronica; Irna Salwa Al Iksani; Mella Anggraeni; Gilar Budi Pratama; Sitty Ainsyah Habibie (Tomini Journal of Aquatic Science, 2025)
Pangandaran Reservoir, located in Pangandaran Regency, West Java, serves as a water conservation facility and supports aquaculture activities. Its water quality, particularly in terms of dissolved oxygen (DO) and biochemical oxygen demand (BOD₅), is a key indicator for maintaining the reservoir's ecological and socio-economic functions. This study aims to analyze DO and BOD₅ parameters in Pangandaran Reservoir and evaluate their compliance with applicable water quality standards. Sampling was conducted in May 2025 at four stations representing both the inflow area and the inner reservoir waters. DO levels were measured using the Winkler titration method, while BOD₅ was determined based on the difference in DO concentrations before and after a five-day incubation period. The results showed that water temperatures ranged from 32 to 32.5°C, slightly exceeding the water quality threshold, likely due to high solar radiation and limited vegetation cover. The pH ranged from 7 to 9, which is still within the safe range, with higher pH values observed in the inflow area, influenced by the dominance of limestone (karst) formations in the surrounding Pangandaran region. The highest DO concentration was recorded at Station 4 (4.32 mg. L-1), while the lowest was at Station 2 (3.40 mg. L-1). Conversely, the highest BOD₅ values were found at Station 2 (8.3 mg. L-1) and Station 1 (8 mg. L-1). The spatial distribution pattern indicates a negative relationship between DO and BOD₅, where high organic pollutant loads in the inflow area reduce dissolved oxygen levels. Overall, the water quality of Pangandaran Reservoir falls within Class 2 to Class 4 based on Government Regulation No. 82 of 2001, with signs of declining quality in the inflow area. Therefore, pollution source control and routine monitoring are essential to preserve the aquatic ecosystem of the reservoir.